Peningkatan Manajemen dan Sustainable pada Kelompok Mitra Usaha Keripik Tempe Rahayu Mandiri Desa Langse PATI Guna Kompetitif di Pasar Oleh-Oleh Wisata Nasional - Subono, SE., M.Si, Agung; Sumekar, Kertati; Hidayat, Taufiq; Sutono, Sutono (Universitas Muria Kudus, 2024)
This community service aims to support creative economy programs and open employment opportunities through food products in UMKM /MSME. This PKM collaborates with the Rahayu Mandiri Tempe Chips Business Partner Group as partner 1 and Winong Pati Tempe Craftsmen as partner 2. Management and sustainability issues are still not optimal so they require TQM (total quality management) and Applied Technology (teknologi terapan). This service method involves interviewing and providing the necessary training so that PKM products increase their long-term profits and are able to compete with national souvenir food products. Output Results: meet Production Standards for MSME level that have been registered in Pati Regency; Meet the Wage Standards for employees according to the UMR of Pati Regency. Meet licensing standards related to PIRT (pangan industri rumah tangga), or home industrial food, where products are tested in the laboratory for nutritional content. Meet business environmental standards with minimal waste.